(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The aim of the research is to highlight the role of external auditing in assessment of performance of companies by establishing objective indicators to measure their financial and non-financial performance within the dimensions of the Balanced Scorecard (BSC). The research also aims to align with the objectives of auditing in order to assess and evaluate the performance of these companies, analyze their trends, and attempt to understand and clarify their strategies. Through this strategy, the research seeks to identify the goals that the company seeks to achieve and then analyze the proposed indicators within the dimensions of the scorecard to identify areas of strength and weakness. The goal is to leverage areas of strength and address weaknesses to achieve the company’s predetermined objectives. To achieve the research objective, several tools were used, including analyzing the dimensions of the Balanced Scorecard and developing performance evaluation indicators within the framework of these dimensions. The inputs for these indicators were examined to ensure their consistency and reliability through a set of auditing procedures. The research resulted in a set of conclusions, the most important of which is that external auditing has a significant impact on evaluating the performance of companies, both financially and non-financially, and providing valuable advice to management due to the independence of external auditing from company management.